1999
DOI: 10.1111/j.1502-3885.1999.tb00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Postglacial emergence and Late Quaternary glaciation on northern Novaya Zemlya, Arctic Russia

Abstract: Recent observations on postglacial emergence and past glacier extent for one of the least accessible areas in the Arctic, northern Novaya Zemlya are here united. The postglacial marine limit formed 5 to 6 ka is registered on the east and west coasts of the north island at 10 f 1 and 18 f 2 m aht, respectively. This modest and late isostatic response along with deglacial ages of >9.2 ka on adjacent marine cores from the northern Barents Sea indicate either early (>13 ka) deglaciation or modest ice sheet loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 30 publications
(32 reference statements)
6
51
0
1
Order By: Relevance
“…The Late-Glacial and the Holocene Based on dating of Holocene raised shorelines in northern Novaya Zemlya, it is suggested that the Barents Sea ice sheet either melted at c. 13 ka or was thin (Forman et al 1999). A Holocene shore line diagram from just within the Younger Dryas ice sheet boundary in the western Kola peninsula shows the Eiliv Lursen et al…”
Section: Late Weichselianmentioning
confidence: 97%
“…The Late-Glacial and the Holocene Based on dating of Holocene raised shorelines in northern Novaya Zemlya, it is suggested that the Barents Sea ice sheet either melted at c. 13 ka or was thin (Forman et al 1999). A Holocene shore line diagram from just within the Younger Dryas ice sheet boundary in the western Kola peninsula shows the Eiliv Lursen et al…”
Section: Late Weichselianmentioning
confidence: 97%
“…Hiatella is a cosmopolitan genus known since the Eocene (e.g., Zinsmeister, 1984;James and Bone, 2000;Coan et al, 2000) and is an accessory faunal element within temperate and cool-water communities (Coan et al, 2000;Gordillo, 2001), extending well within polar settings. For instance, Hiatella arctica is a common component of Pleistocene to Recent Arctic and sub-Arctic marine communities, inhabiting a variety of shallow environments (e.g., Ocklemann, 1958;Hillaire-Marcel, 1981;Hétu, 1998;Forman et al, 1999;Gordillo and Aitken, 2000;Miller et al, 2002;Lajeunesse and Allard, 2003;Kaufman et al, 2004). Hiatella is known to be a dominant element of truly polar Arctic communities where it may form almost monotypical assemblages within high-arctic fjords attaining higher biomass in shallow waters (Petersen et al, 2001;Sejr et al, 2002).…”
Section: Mollusc Paleoenvironmentmentioning
confidence: 97%
“…Unaltered Hiatella carbonate is suitable for aminoacid dating and is widely used to assess chronology in the Arctic (Kaufman and Manley, 1998;Sejrup et al, 1999;Forman et al, 1999;Kaufman et al, 2004). The amino acid D / L ratios obtained from the four in situ mollusc samples (PCM-00-6, 82, 155 and 168) range from 0.569 and 0.622, which are very low for Miocene material.…”
Section: Geochronology and Deposition Ratesmentioning
confidence: 99%
“…4.6). Climate aridization is fixed on the surrounding land during LGM (Velichko et al 1997;Serebryanny et al 1998;Velichko 1999;Forman et al 1999;Polyak et al 2000a). Climate aridization is fixed on the surrounding land during LGM (Velichko et al 1997;Serebryanny et al 1998;Velichko 1999;Forman et al 1999;Polyak et al 2000a).…”
Section: The End Of the Last Glaciationmentioning
confidence: 99%